Evaluating the Rutting Resistance of Asphalt Concrete Modified With Organo-Philic Montmorillonite Nano-Clay - Micheal Gamukama (Uganda Christian University, 2025)
Asphalt pavements are required to have long-term performance and durability to keep highway traffic safe and protected from damage from serious failures such as rutting which is described as the permanent deformation of the pavement surface in the area of the wheel path (Huang, 2012).This was the primary reason this research was conducted based on the idea that OMMT could potentially be used to increase the mechanical and volumetric properties and, therefore, the rutting resistance of the asphalt mixture. Unlike previous studies that concentrated on using montmorillonite in its untreated form, this research investigated the use of surface-modified OMMT to improve OMMT compatibility with the bituminous binder. Results from the laboratory indicated that adding 1% OMMT by weight of aggregate achieved significant improvements in the asphalt mixture's Marshall Stability (17.2 kN) and Flow Value (3.6 mm) as well as the Air Voids Content (4.2%), Voids in Mineral Aggregate Value (15.3%), Voids Filled with Bitumen Value (72.4%), and Bulk Density Value (3.352). A comprehensive literature review identified the mechanisms that cause rutting in pavements and evaluated the structural response of pavements to loading, and indicated that the physical and performance-related characteristics of the asphalt mixtures tested were adequate to meet asphalt pavement performance requirements and supported an increase in their deformation resistance. Additionally, the standard mechanical tests indicated that adding OMMT to the asphalt mixture hindered rutting and created a more uniform distribution of applied loads. These results suggest that the use of Binders that use Nanotechnology such as OMMT is a more efficient method to increase the load-carrying ability of Ugandan Highways, allowing them to last longer and reduce maintenance expenses.